PENGEMBANGAN BIOSENSOR ELEKTROKIMIA BERBASIS ENZIM ASETILKOLINESTERASE UNTUK ANALISIS RESIDU PESTISIDA PADA PRODUK PERTANIAN - Mashuni, Mashuni (Jurnal Agroteknos, 2012)
Pesticide is one of dangerous chemical compounds in environment. Its existence has spread so it can cause negative effect for human. Pesticide compound is toxic in for nervous system so that a quick detection system is needed to protect human’s health and as a control for agricultural product. Therefore, we conducted a research of electrochemical biosensors development based on enzyme acetylcholinesterase in electrode to analyze pesticide residue so that a more superior and reliable biosensors can be obtained for pesticide residue analysis in foodstuff samples, especially for agricultural product. Residue analysis of carbamate and organophosphate in foodstuff sample requires a sensitive, selective, cheap- and-easy-operated, and quick-analyzed tools. A new research has been designed in making of biosensors electrode by using immobilization method of enzyme acetylcholinesterase (AChE) with the supporting materials of Acetate Selulose (AS) and Glutaraldehid (GA) in biosensor electrode connected with electrochemical transducer. Designed biosensors were characterized, including Nernst factor, the detection limit, response time, and period of use. Next, biosensors were tested in sample of vegetables and fruits. Expected result was a biosensor prototype with better work than pesticide determination with instrument of Gas Chromatography (GC) and High Pressure Liquid Chromatography (HPLC). Biosensor development offers low cost, accurate, quick analysis time, and sensitive to detect pesticide residue. Keywords: : Pesticide, Biosensor, Electrochemical, Enzim, Sensitive